2021
DOI: 10.3389/fonc.2021.632956
|View full text |Cite
|
Sign up to set email alerts
|

Mechanobiology of Autophagy: The Unexplored Side of Cancer

Abstract: Proper execution of cellular function, maintenance of cellular homeostasis and cell survival depend on functional integration of cellular processes and correct orchestration of cellular responses to stresses. Cancer transformation is a common negative consequence of mismanagement of coordinated response by the cell. In this scenario, by maintaining the balance among synthesis, degradation, and recycling of cytosolic components including proteins, lipids, and organelles the process of autophagy plays a central … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 280 publications
(324 reference statements)
0
33
0
Order By: Relevance
“…In addition to directly inhibiting mechanical signal transduction, another feasible approach is to target the downstream molecular mechanisms and cellular processes that promote disease progression. One such target is autophagy which has been implicated in treatment resistance in various cancers including GBM (138)(139)(140). Recent studies have shown that the process of autophagy is altered by mechanical stimuli and signal transduction primarily through two mechanisms: 1) crosstalk between the shared regulatory proteins in autophagy and mechanical signal transduction pathway or 2) competition for molecular substrates utilized in both processes such as cytoskeletal elements (138).…”
Section: Theranostic Opportunities and Modeling Therapeutic Targetsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to directly inhibiting mechanical signal transduction, another feasible approach is to target the downstream molecular mechanisms and cellular processes that promote disease progression. One such target is autophagy which has been implicated in treatment resistance in various cancers including GBM (138)(139)(140). Recent studies have shown that the process of autophagy is altered by mechanical stimuli and signal transduction primarily through two mechanisms: 1) crosstalk between the shared regulatory proteins in autophagy and mechanical signal transduction pathway or 2) competition for molecular substrates utilized in both processes such as cytoskeletal elements (138).…”
Section: Theranostic Opportunities and Modeling Therapeutic Targetsmentioning
confidence: 99%
“…One such target is autophagy which has been implicated in treatment resistance in various cancers including GBM (138)(139)(140). Recent studies have shown that the process of autophagy is altered by mechanical stimuli and signal transduction primarily through two mechanisms: 1) crosstalk between the shared regulatory proteins in autophagy and mechanical signal transduction pathway or 2) competition for molecular substrates utilized in both processes such as cytoskeletal elements (138). Several common pathways have been described in the literature and include the YAP/TAZ axis, JAK-mediated signal transduction, and the expression of EGFR (138,141,142).…”
Section: Theranostic Opportunities and Modeling Therapeutic Targetsmentioning
confidence: 99%
See 1 more Smart Citation
“…Epithelial cells are susceptible to several mechanical stimuli resulting from the cell-to-cell interactions and the extracellular matrix (e.g., composition, stiffness, and density), as well as fluid pressure and lateral stretch and compression required for the physiological function of several organs [ 168 ].…”
Section: Autophagy and Emtmentioning
confidence: 99%
“…Such resistance mainly originates from an "autophagy" mechanism in the cell. [14,15] Autophagy represents an important cellular pathway that breaks down impaired organelles, aged proteins and other constituents, reusing them as cellular nutrients for self-renewal. [16,17] Additionally, autophagy has a vital function in resisting cell stress as well as various treatment methods.…”
Section: Introductionmentioning
confidence: 99%